Linguo-cognitive models in mini-format texts in English educational discourse (based on «English Unlimited» textbook, Advanced) - V. D. Shevchenko; E. V. Yakovleva (Вестник Самарского университета: История, педагогика, филология, 2023)
The article deals with cognitive models analysis of situations represented in mini-format texts from English educational discourse. The research is based on the texts from the coursebook English Unlimited Advanced. The method implied has been the cognitive modelling developed by the American linguist Dell Hymes. This includes the representation of communicative situation via meaningful constituents like Participants, Act and Sequence, Setting and Scene, Tone, Key, Instrumentalities and others. The aim of the research is to reveal the dominant components of linguo-cognitive models and their pragmatic and communicative functions. It has been revealed that the dominant components of the analyzed situations are Participants and, Key. The authors highlight these components with the help of the language means that aim at realizing emotive and affective function. It has also been revealed that the mini-format texts at the Advanced level contain more comprehensive implications, thus students must decode main themes and ideas not only with the means of the English language but also using their background knowledge and specific cognitive scenarios from their memory.